Heat transfer in unconventional geothermal wells: a double numerical modelling approach - Renaud, Théo; Verdin, Patrick; Falcone, Gioia (Springer, 2021)
Geothermal energy aims at producing electricity or heat from underground resources. Worldwide geothermal energy extraction and use is still limited, despite its estimated high potential. To date, the efficiency and viability of enhanced geothermal system (EGS) and deep unconventional geothermal resources (e.g. superheated/supercritical systems) via conventional heat recovery techniques have led to limited success due to technology issues. Research on superheated/supercritical geothermal systems is highly active in Europe, notably triggered by the Iceland Deep Drilling Project (IDDP) [1]. Supercritical resources could deliver more energy than conventional resources thanks to the increase of enthalpy and the sharp decrease of density around the critical point of water [2]. The first well from IDDP was drilled at a depth of 2072 m after unintentionally drilling into magma between 2092 and 2104 m. The wellhead temperature reached 450°CC, with a superheated steam at a pressure of 140 bars (Palsson et al. in Geothermics 49:23–30, 2014).